The Influence of Good Corporate Governance, Corporate Social Responsibility, and Sustainability Reporting Disclosure on Financial Performance - Ibrahim; Mulyana Machmud; Nur Rahmadani; Hasanuddin (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The mining sector significantly contributes to Indonesia’s economic growth but faces challenges in financial stability, governance, and social and environmental responsibility. This study examines the impact of good corporate governance, corporate social responsibility, and sustainability reporting on the financial performance of mining companies listed on the Indonesia Stock Exchange from 2020 to 2022. Using secondary data from IDX financial reports, 18 firms were selected through purposive sampling. Data analysis involved assumption testing, multiple linear regression, and hypothesis testing using SPSS 26. Results indicate that good corporate governance positively and significantly affects financial performance, suggesting that strong governance enhances financial outcomes. In contrast, corporate social responsibility and sustainability reporting do not show significant effects, implying that social and sustainability initiatives have yet to translate into measurable financial gains. The findings suggest that mining companies should strengthen governance practices to improve transparency and investor confidence, while enhancing the quality and implementation of corporate social responsibility and sustainability reporting to create greater long-term economic value.